Sifat-sifat Kimia dan Mineralogi Tanah serta Kaitannya dengan Kebutuhan Pupuk untuk Padi (Oryza sativa), Jagung (Zea mays), dan Kedelai (Glycine max) - Dedi Nursyamsi; , Suprihati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Laboratory experiment was conducted to identify soil chemical and mineralogical characteristics from topsoil (0-20 cm) of Inceptisols, Oxisols, Vertisols, and Andisols, as well as its relationship with the requirement of NPK, lime, and organic matter fertilizers for rice, maize, and soybean at laboratory of Indonesian Soil Research Institute and Soil Science Department of Bogor Agricultural University. The result showed that Inceptisols was dominated by kaolinite (1:1), Oxisols by kaolinite and goethite (hydroxide), and Vertisols by smectite (2:1). Andisols had kaolinite and crystobalite (oxide) minerals in it, while amorphous materials could not be detected through X-ray Diffraction (XRD) method. The soil reaction of Inceptisols, Oxisols, and Andisols was acid; exchangeable (exch) Ca and Mg, the contents of K and P, as well as base saturation (BS) of the soils were low. On the contrary, the soil reaction of Vertisols was neutral; exch. Al and H were very low, whereas exch. Ca and Mg, the contents of K and P, as well as base saturation (BS) of the soil were high. Both Vertisols and Andisols had high cation exchange capacity (CEC) which was from permanent charge in Vertisols and from variable charge (organic matter) in Andisols. Fertilizer requirement for crops in the soil was affected by land use system, plant species, soil nutrient content and its behavior in the soil system. Key words: Soil characteristics, fertilizer, rice, maize, soybean.